2004
DOI: 10.1111/j.1443-1661.2005.00452.x
|View full text |Cite
|
Sign up to set email alerts
|

Oblique‐viewing Endoscope Facilitates Endoscopic Retrograde Cholangiopancreatography and Associated Procedures in Post‐billroth Ii Gastrectomy Patients

Abstract: Background : Endoscopic retrograde cholangiopancreatography (ERCP) and associated procedures have been reported to be difficult to perform in patients with Billroth II gastrectomy. We evaluated the feasibility of using an oblique-viewing endoscope equipped with a cannula deflector for these procedures in such patients. Patients and Methods : Twenty-four patients with Billroth II gastrectomy were enrolled in the present study and underwent ERCP, endoscopic sphincterotomy, endoscopic nasobiliary drainage, expand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 14 publications
1
34
0
Order By: Relevance
“…We achieved a high success rate of cannulation of the bile duct by using an anterior oblique-viewing endoscope. Kikuyama et al 3 reported the results of the use of an anterior oblique-viewing endoscope in ERCP and associated procedures in cases with B-II gastrectomy. They succeeded in reaching the papilla in 22 of 24 cases (91.7%) with the scope, and cannulation of the bile duct was successful in all 22 cases.…”
Section: Duct Clearancementioning
confidence: 98%
See 2 more Smart Citations
“…We achieved a high success rate of cannulation of the bile duct by using an anterior oblique-viewing endoscope. Kikuyama et al 3 reported the results of the use of an anterior oblique-viewing endoscope in ERCP and associated procedures in cases with B-II gastrectomy. They succeeded in reaching the papilla in 22 of 24 cases (91.7%) with the scope, and cannulation of the bile duct was successful in all 22 cases.…”
Section: Duct Clearancementioning
confidence: 98%
“…Several other techniques, including the use of a doubleballoon enteroscope 17,18 or an anterior-viewing endoscope with a transparent cap attached to its tip, 15,19,20 have been reported. Only one study discusses the efficacy of an anterior oblique-viewing endoscope in ERCP and associated procedures in patients with B-II gastrectomy, 3 and its effi cacy and safety have not yet been clarifi ed.…”
Section: Duct Clearancementioning
confidence: 99%
See 1 more Smart Citation
“…In the patients for whom the fiber reached the papilla in this study, the success rate of cannulation was as high as 90.9%. This report does not have inferiority in comparison with the results of an anterograde oblique-viewing endoscope[21,22]. The reason why the success rate was high despite that this patient represented a case with difficulty in cannulation, in which the papilla existed on the opposite side from the usual one, was because the flexible tip catheter[23], etc ., with which the angle can be changed in cannulation, was used.…”
Section: Discussionmentioning
confidence: 84%
“…However, with a forward-viewing endoscope, identifying the anastomosis and cannulating the main pancreatic duct via the anastomosis were difficult because of the sharp angulation required to observe the intestinal wall and the lack of a cannula deflector. 8 Under these considerations, an oblique-viewing endoscope that facilitates ERCP in Billroth II 13,14 or Roux-en-Y reconstruction 15 is considered ideal to cannulate the main pancreatic duct via the stenotic pancreatojejunostomy because it has a cannula deflector with good visibility for advancing into the GI lumen and observing the intestinal wall.…”
Section: Discussionmentioning
confidence: 99%